Skrining Fitokimia Ekstrak Etanol Daun Kersen (Muntingia Calabura) - Syahara, Suci; Siregar, Yenni Farida (Jurnal Kesehatan Ilmiah Aufa Royhan, 2019)
Plants that contain secondary metabolite compounds are Muntingia calabura L. or so-called cherry plants. Cherry plants are neotropic plants. This plant originated from the Philippines and was reported to enter Indonesia at the end of the 19th century. According to Arum et al. (2012), cherry leaves contain a group of compounds including flavonoids, triterpenoids, and saponins. Khrisnaveni (2014) reported the content of cherry leaves consisting of alkaloids, flavonoids, and anthraquinone. The content of compounds owned by cherry leaves is thought to have anticancer bioactive compounds, so it needs preliminary tests through cytotoxic tests. Cytotoxic test is one of the development methods to predict the presence of toxic compounds in cells (Kurnijasanti et al., 2008). One method to determine the toxic nature of natural ingredients is the Brine Shrimp Lethality Test (BSLT) method. BSLT method is one of the toxicity test methods used in tracing toxic bioactive compounds from natural materials. This method was chosen because it is cheap, fast, and easy to do. BSLT is used as a preliminary test in the search for anticancer compounds, which if positive results can be continued testing on human cancer cells.